V‐SYMPHONY career development series: A collaboration to enhance professional awareness for pediatric hematology oncology trainees. Issue 3 (26th December 2022) - Tal, Adit L.; Bailey, Kayleen A.; Chou, Alexander; Offer, Katharine; Rosenblum, Jeremy; Moerdler, Scott; Askew, Megan; Roberts, Stephen; Vagrecha, Anshul; Orsey, Andrea; Robbins, Gabriel; Satwani, Prakash; et al.
Abstract: Background: A recent survey of pediatric hematology oncology (PHO) physicians identified that a majority believe fellows are struggling to find jobs that align with their goals. Career development for trainees has historically been home institution‐specific, limiting fellows' exposures to career path possibilities. The "virtual‐Symposium of Pediatric Hematology/Oncology of New York (v‐SYMPHONY)" instituted a tristate Career Development Series for PHO trainees to better address their needs and increase awareness of the variety of PHO career opportunities. Procedure: The v‐SYMPHONY Career Development Series incorporated three sessions: (a) institutional perspective, (b) individual perspectives, and (c) nuts and bolts of job search. Pre‐ and post‐series surveys were administered to participants to measure impact. Results: Forty‐one fellows registered for the series and completed a pre‐survey. Over half (54%) were in their third or later year of fellowship. Careers with a clinical focus were the most commonly desired career path (59%). Most had received career development advice only from faculty within their institutions (90%). Post‐surveys were completed by 11 PHO fellows. Overall, 100% of respondents reported benefiting from the career sessions and recommended the series should be repeated annually. Over 90% learned new information to prepare for the job search. Conclusions: The v‐SYMPHONY Career Development Series for PHO fellows across multiple institutions was established and was extremely well received by its participants. PHO fellows agreed that these sessions were beneficial in helping prepare them for the job search process. An annual regional Career Development Series is feasible and is strongly suggested to support PHO fellows.